A Cost‐Benefit Analysis of Medical Scribes and Electronic Medical Record System in an Academic Urology Clinic. Issue 3 (May 2015) - Carnes, Kevin M.; de Riese, Cornelia S.; de Riese, Werner T.W.
Abstract : Introduction: : Electronic medical records have introduced an additional level of complexity to the patient‐provider encounter and medical scribes may offer a solution. We examined how a medical scribe system could support an academic urology clinic. To assess the financial feasibility of this model, we analyzed the additional costs associated with adding medical scribes and we discuss the potential benefits of this system. Methods: : We measured total patient wait and interaction times with staff, and estimated the additional staff required to maintain an increased patient load if medical scribes were introduced. We then calculated the average revenue per patient during the most recent 9 months of data to estimate the minimum increase in the number of patient visits needed to offset the additional staffing needs. Results: : Mean ± SD total wait time was 23 minutes 28 seconds ± 13 minutes 4 seconds. Average monthly expenses would increase by $17, 452.50 for 6 additional staff members, including 1 nursing assistant, 1 patient service specialist, 1 nurse and 3 scribes. There was an average of 666 monthly office visits and average net revenue to the department was $107.78 per patient visit. The increase in the number of patient visits required to break even would be 162 additional patients per month, representing a 24.3% increase. Additional downstream revenue was considered. Conclusions: : A medical scribe system in the example of an academic urology clinic setting could increase patient flow and decrease the burden on medical providers by reducing computer charting. This model is only financially prudent if the increased expenses are offset by additional revenue from increased patient visits.